MENINGKATKAN MOTIVASI PESERTA DIDIK MELALUI MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV DI SDN 112/I PERUMNAS - Ema Nur Amalia; Meideka Sapriani; Arrum Dwi Wahyuni; Risdalina; destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students’ learning motivation in the Indonesian language subject through the implementation of the Problem Based Learning (PBL) model supported by audio-visual media in grade IV at SDN 112/I Perumnas. The background of this research is the low level of student motivation, as indicated by a lack of interest, enthusiasm, responsibility, and satisfaction in participating in the learning process. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. Data were collected through observations based on five indicators of learning motivation. The results of the study showed a significant increase in students’ motivation after the implementation of the PBL model with audio-visual media support. In the pre-action stage, the average motivation was in the low category with a percentage of 49%. After the first cycle, it increased to 60.8% (moderate category), and in the second cycle, it rose to 81.25% (good category). The application of the PBL model encouraged students to be more active, interested, and responsible in learning activities, while audio-visual media helped enhance students’ understanding and interest in the subject matter. Thus, it can be concluded that the Problem Based Learning model supported by audio-visual media is effective in improving students’ learning motivation and is recommended as an innovative learning strategy for primary education.